2015
DOI: 10.1515/amm-2015-0070
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Al-Cu Bimetallic Bars Properties After Explosive Welding and Rolling in Modified Passes

Abstract: The paper presents the results of the experimental tests of Al-Cu bimetallic bars rolling process in multi-radial modified passes. The bimetallic bars consist of aluminium core, grade 1050A and copper outer layer, grade M1E. The stocks were round bars with diameter 22 mm with a copper layer share of 15 and 30%. As a result of rolling in four passes, bars of a diameter of about 16.0 mm were obtained. A bimetallic stock was manufactured using an explosive welding method. The use of the designed arrangement of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…From investigations carried out it was found that using explosion cladding produced bimetallic feedstocks with a Cu layer share in the bar cross‐section of 15 and 30 %, which were characterized by a slight unevenness of Cu layer distribution along the aluminium core perimeter of approx. 10 % . The obtained unevenness might have been the sum of the initial unevenness of the wall of the Cu tube used for explosion cladding and the ovality of the aluminium bars from which the cores were made.…”
Section: Comparative Analysis Of the Results Of The Theoretical And Ementioning
confidence: 99%
See 1 more Smart Citation
“…From investigations carried out it was found that using explosion cladding produced bimetallic feedstocks with a Cu layer share in the bar cross‐section of 15 and 30 %, which were characterized by a slight unevenness of Cu layer distribution along the aluminium core perimeter of approx. 10 % . The obtained unevenness might have been the sum of the initial unevenness of the wall of the Cu tube used for explosion cladding and the ovality of the aluminium bars from which the cores were made.…”
Section: Comparative Analysis Of the Results Of The Theoretical And Ementioning
confidence: 99%
“…These small differences might have resulted from the mathematical model employed for numerical quality failing to consider the quality and nature of the joint, as well as the intermediate layers occurring within the joint zone. It should be noted, at the same time, that the hard transition layer CuAl 2 occurring in the explosion‐cladded feedstock may affect the pattern of bimetal plastic flow in the roll gap . The increase in the hard cladding layer fraction of the aluminium core perimeter and the occurrence of the CuAl 2 transition layer, being several times harder than the copper cladding layer, will increase the tendency of the Al–Cu bimetallic band to widening, compared to the homogeneous aluminium bar.…”
Section: Comparative Analysis Of the Results Of The Theoretical And Ementioning
confidence: 99%
“…3) allows larger deformations and elongations to be applied in the rolling process, compared to the case where classical stretching passes are used [12,13]. As a result of modifying the shape of the passes, a change in the mode of material plastic flow takes place, that contributes to the occurrence of more uniform of stress and strain distribution on the cross-section of the band than in the case of rolling in classical stretching passes.…”
Section: The Rolling Processesmentioning
confidence: 99%
“…The most commonly used methods include diffusion bonding [14,15], hot pressing [16,17], extrusion [18,19], rolling [20,21] and rolling in grooves [22,23], explosive welding [24,25], forging [26,27], and two-roll casting [28]. Additionally, in this case, some of the mentioned methods do not guarantee the right quality of the joint, the required thickness of the plating layer, and, in addition, in the case of round bimetallic bars, even distribution of the plating layer around the core perimeter [29,30]. The most frequently used methods to produce round bimetallic bars include extrusion [18,19,31] and rolling in grooves [23,30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in this case, some of the mentioned methods do not guarantee the right quality of the joint, the required thickness of the plating layer, and, in addition, in the case of round bimetallic bars, even distribution of the plating layer around the core perimeter [29,30]. The most frequently used methods to produce round bimetallic bars include extrusion [18,19,31] and rolling in grooves [23,30,32]. The feedstock for these processes is made directly in the processes themselves, as in the case of extrusion [18,19] or with the possibility of earlier use of the casting method [22] or explosive welding [30,32].…”
Section: Introductionmentioning
confidence: 99%